Fragments of grammatical facilitation in the writings of Dr. Khalil Bunyan Al-Hassoun (Journal of Imam Al-Kadhim College, 2023)
Abstract:     This paper aims to discover the facilitating pauses that Dr. Khalil Bunyan Al-Hassoun stopped during his criticism of the syntacticians  as they cite with the Holy Qur’an and the noble hadith of the Prophet. It is more like the fragments that encrust a part of the ring and do not occupy all of its parts, so we follow these opinions (fragments) in some of Dr. Khalil’s books, such as: (syntacticians and the Qur’an, Glimpses of Verses, syntacticians and Hadith ).Keywords: facilitation, facilitating attempts, abuse, interpretation and interpretation, Dr. Khalil Bunyan Al-Hassoun.
Keywords: : facilitation, facilitation attempts, abuse, interpretation and interpretation, Dr. Khalil Bunyan Al-Hassoun